Expression of FGFs during early mouse tongue development - Du, Wen; Prochazka, Jan; Prochazkova, Michaela; Klein, Ophir D (Gene expression patterns, 2016)
The fibroblast growth factors (FGFs) constitute one of the largest growth factor families, and several ligands and receptors in this family are known to play critical roles during tongue development. In order to provide a comprehensive foundation for research into the role of FGFs during the process of tongue formation, we measured the transcript levels by quantitative PCR and mapped the expression patterns by in situ hybridization of all 22 Fgfs during mouse tongue development between embryonic days (E) 11.5 and E14.5. During this period, Fgf5, Fgf6, Fgf7, Fgf9, Fgf10, Fgf13, Fgf15, Fgf16 and Fgf18 could all be detected with various intensities in the mesenchyme, whereas Fgf1 and Fgf2 were expressed in both the epithelium and the mesenchyme. Our results indicate that FGF signaling regulates tongue development at multiple stages.
Keywords: Animals; epitel; fibroblastové růstové faktory; Embryo, Mammalian; organogeneze; hybridizace in situ; Gene Expression Regulation, Developmental; Fibroblast Growth Factors; Mice; Organogenesis; signální transdukce; myši; Signal Transduction; Epithelium; Mesoderm; Embryonic Development; mezoderm; In Situ Hybridization; jazyk; zvířata; embryonální vývoj; vývojová regulace genové exprese; embryo savčí; Tongue